Does Adulthood Obesity Promote Greenhouse Gas Emissions in Africa? Evidence from Panel Corrected Standard Error Models - Oyekale, Abayomi Samuel (Acta Universitatis Danubius. Œconomica, 2024)
Obesity is one of the major public health epidemics that the world currently faces. The environmental implication of obesity is reflected in its impacts on greenhouse gas (GHG) emissions due to increased pressure on food production system, oxidative metabolism, and combustion of fossil fuels during transportation. However, few studies exist on the linkage between GHG emissions and obesity. This seeks to fill this gap by analyzing the effect obesity total GHG emission, carbon dioxides emissions, per capita carbon emissions, and emissions of carbon dioxide from liquid fuel. The data were from 45 African countries for the period 1990-2016. The data were analyzed with panel corrected standard error (PCSE) after positive feedbacks from cross-section dependence, and cointegration tests. The results showed that obesity, urban population, and GDP per capita were generally positively related to GHG emissions, while renewable energy, livestock production index and utilization had negative association. It was recommended that initiatives to reduce obesity promise some environmental benefits. Also, there is the need to promote renewable energy utilization and facilitate sustainable agricultural production, to reduce environmental damages.